Comparison of catheter-associated quality of life in external urinary diversion: nephrostomy vs. suprapubic catheter Vergleich der katheterassoziierten Lebensqualität bei externen Harnableitungen: Nephrostomie vs. suprapubischer Katheter - Wiedemann, A.; Weinhofer, M.; Stein, J.; Linné, C.; Kirschner-Hermanns, R.; Schorn, A.; Wagner, A.; Moll, V.; Unger, U.; Salem, J.; Liebald, T.; Bannowsky, A.; et al. (Urologe, 2022)
Introduction: A percutaneous nephrostomy (PCN) affects the integrity of the patient due to the requirement of an external drainage bag and regular changes. The catheter-associated quality of life (QOL) was evaluated using a validated assessment and compared to similar patients with suprapubic bladder drainage. Methods: A validated assessment analyzing catheter-related QOL for 5 domains and 25 individual items (first published by Mary Wilde) was completed during a catheter change appointment by patients who had their unilateral or bilateral PCN for a minimum of 3 months in life-long indication. Results: In 66 patients (unilateral PCN: 42 patients), a moderate impairment of their catheter-related QOL was shown. The overall QOL score was median 4.0 on a scale of 0–5. This was rated lower—indicating a stronger impairment of QOL—than in patients with a suprapubic bladder catheter, who had a median score of 4.3. Significant differences were found related to the catheter type in the items “feeling of humiliation due to the PCN”, “conflicts with the medical or nursing staff”, “fear of painful catheter changes”, “feeling ill”, “being handicapped in activities of daily living” and “concern of not being able to do what one wants to do” and “fear of catheter leakages”. The indication for the PCN due to a malignant or benign underlying disease was not associated with the catheter-related QOL. Conclusion: For the first time, the catheter-related QOL was found to be moderately impaired in patients with a PCN using a validated assessment. Affected individuals report feeling “ill” and “limited/disabled” in activities of daily living; thus, the surgical indication should be strict. Fear of painful catheter changes and of catheter leakages indicates the need of technically correct catheter changes.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Catheter-associated quality of life; Geriatric patients; Palliative care; Percutaneous nephrostomy; Suprapubic catheter